Morality and global justice : justifications and applications - Boylan, Michael, 1952- (Westview Press, 2011)
"Boylan makes a daring effort to take on the broad scope of global ethics in a manageable and comprehensive way. His introduction of the worldview imperatives in this context is imaginative and offers a way of engaging students while holding them accountable for their views."---Robert Paul Churchill, George Washington University --